Exchange Rate Pass-Through, Currency of Invoicing and Market Share - Michael B. Devereux; Wei Dong; Ben Tomlin (Bank of Canada, 2015)
This paper investigates the impact of market structure on the joint determination of exchange rate pass-through and currency of invoicing in international trade. A novel feature of the study is the focus on market share of firms on both sides of the market - that is, exporting firms and importing firms. A model of monopolistic competition with heterogeneous firms has the following set of predictions: a) exchange rate pass-through should be non-monotonic and U-shaped in the market share of exporting firms, but monotonically declining in the market share of importers; b) exchange rate pass-through should be lower, the higher is local currency invoicing of imports; and c) producer currency invoicing should be related non-monotonically and U-shaped to exporter market share, and monotonically declining in importing firms' market share. We test these predictions using a new and large micro data set covering the universe of Canadian imports over a six-year period. The data strongly support all three predictions.
Keywords: F3; F4; 330; Exchange rates; Inflation and prices; Market structure and pricing